Effectiveness of Technology Application in Health Service System to Improve the Quality of Life of Elderly People with Chronic Disease - Maria Carisita Suci Puspa Pranasari; Wahyu Aditama (Jurnal Locus Penelitian dan Pengabdian, 2026)
The rapid advancement of technology has significantly transformed healthcare services, particularly in improving the quality of life for elderly individuals with chronic diseases. However, the effectiveness of these technologies depends on the digital literacy of users, which remains low among the elderly. This study employed a qualitative case study approach to evaluate the effectiveness of technology applications at Keputih Community Health Center in Surabaya, Indonesia, and to analyze the digital literacy of elderly chronic disease patients. Data were collected through semi-structured interviews with six elderly informants, observations, and secondary health data from Electronic Health Records (EHR), Non-Communicable Disease Information System (SPTM), and ECLAIM Primary Care applications. The findings reveal two main results: first, elderly patients face significant barriers in digital skills (downloading apps, uploading files, searching for information) and digital safety (controlling privacy settings, identifying malware, creating secure passwords), requiring assistance from family members or health cadres. Second, despite these barriers, elderly hypertension patients demonstrated higher treatment adherence and better blood pressure control compared to productive-age patients. The implications suggest that while digital health applications benefit chronic disease management, they must be accompanied by tailored digital literacy training and family-based assistance to maximize their effectiveness for elderly populations. The study contributes to the literature on digital health equity and elderly care in low-resource settings.